National Health Interview Survey on Disability, 1995: Phase II, Adult Followback ([Verlag nicht ermittelbar], 1999)
The purpose of the National Health Interview Survey (NHIS) is to obtain information about the amount and distribution of illness, its effects in terms of disability and chronic impairments, and the kinds of health services people receive. The National Health Interview Survey on Disability (NHIS-D), first administered in 1994, was designed to collect data that can be used to understand disability and develop public policy. Another goal of this survey was to find a balance among medical, administrative, and social issues involved in disability measurement. The 1995 NHIS-D was conducted in two phases. Phase I was administered at the same time as the 1995 NHIS core. The Phase I Disability questionnaire elicited information on disability and was used as a screening device for Phase II. Phase II has two parts, a Child file and an Adult file. The Adult Followback file includes questions on housing and long-term care services, transportation, social activity, work history/employment, vocational rehabilitation, assistive devices and technologies, health insurance, assistance with key activities, self-direction, family structure, relationships, living arrangements, conditions and impairments, health opinions and behaviors, community services, and proxy status. This file can be linked to the 1995 NHIS core data (ICPSR 2533). In addition, it can be linked to NATIONAL HEALTH INTERVIEW SURVEY ON DISABILITY, 1995: PHASE I, PERSON AND CONDITION DATA (ICPSR 2562), NATIONAL HEALTH INTERVIEW SURVEY, 1995: ACCESS TO CARE SUPPLEMENT (ICPSR 2525), and NATIONAL HEALTH INTERVIEW SURVEY, 1995: HEALTH INSURANCE SUPPLEMENT (ICPSR 2530).